Mutation of PFN1 Gene in an Early Onset, Polyostotic Paget-like Disease - Merlotti, Daniela; Materozzi, Maria; Bianciardi, Simone; Guarnieri, Vito; Rendina, Domenico; Volterrani, Luca; Bellan, Cristiana; Mingiano, Christian; Picchioni, Tommaso; Frosali, Alessandro; Orfanelli, Ugo; Cenci, Simone; et al. (The journal of clinical endocrinology and metabolism, 2020)
Abstract Context Paget disease of bone (PDB) is a metabolic bone disease whose genetic cause remains unknown in up to 50% of familial patients. Objective Our aim was to investigate the underlying genetic defect in a large pedigree with a severe, early onset, autosomal dominant form of PDB across 3 generations. Methods Whole exome sequencing was performed in affected and unaffected family members, and then mutation screening was replicated in a sample of PDB patients with early-onset, polyostotic PDB. Results We identified a frameshift D107Rfs*3 mutation in PFN1 (encoding for profilin 1, a highly conserved regulator of actin-polymerization and cell motility) causing the truncation of the C-terminal part of the protein. The mutation was also detected in a 17-year-old asymptomatic family member who upon biochemical and radiological analyses was indeed found to be affected. Sequencing of the entire PFN1 coding region in unrelated PDB patients identified the same mutation in 1 patient. All mutation carriers had a reduced response to bisphosphonates, requiring multiple zoledronate infusions to control bone pain and achieve biochemical remission over a long term. In vitro osteoclastogenesis in peripheral blood mononuclear cells (PBMCs) from mutation carriers showed a higher number of osteoclasts with PDB-like features. A similar phenotype was observed upon PFN1 silencing in murine bone marrow-derived monocytes, suggesting that the frameshift PFN1 mutation confers a loss of function in profilin 1 activity that induces PDB-like features in the osteoclasts, likely due to enhanced cell motility and actin ring formation. Conclusions Our findings indicate that PFN1 mutation causes an early onset, polyostotic PDB-like disorder.